IMPROVEMENT OF THE METHODOLOGY FOR DESIGNING TECHNOLOGICAL LINES FOR SAUSAGE PRODUCTION - BATRACHENKO, OLEXANDR; TUNIK, ELENA; PARKHOMENKO, DARIYA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The aim of the work is to improve the methodology for designing technological lines for sausage production, which would provide a significant increase in the accuracy of determining the required productivity of technological equipment and its quantity, taking into account modern requirements of food technology and industrial sanitation for different types of production organization. It was found that the duration of the actual working time allocated to the operation of a particular type of technological equipment during one-, two- and three-shift operation of the enterprise in accordance with the technological process schedule can be 37-62% of the duration of the working shift. It was determined that the duration of technological processing cycles at various technological operations according to modern technological regulations can significantly differ from those values given in the known literature. Thus, the duration of cutting minced meat for sausage products of the cooked group can reach 20-30 minutes, in contrast to 10 minutes in known literary sources. It was found that the duration of auxiliary operations during cutter cutting, depending on the size of the cutter, can be 0056 - 0340 min, and cutters of smaller size correspond to a shorter duration of auxiliary operations. The share of auxiliary operations during cutter cutting and mince mixing can reach 30% of the total duration of the raw material processing cycle in these machines. On the other hand, the duration of auxiliary operations during heat treatment of sausage products can be neglected when designing technological lines, given that the duration of auxiliary operations is 3-5 min, and the duration of technological processing is 1.5-4 hours. It was found that, in accordance with modern sanitary and hygienic standards of the HACCP system, a significant part of the work shift is occupied by the sanitation of technological equipment. Thus, for cutters, the total time spent on sanitation of the machine can take 1-1.5 hours per shift. Similarly, in the case of a round-the-clock operation of a sausage factory, the duration of sanitizing thermal chambers can reach 2 hours. It has been established that according to the proposed methodology for designing sausage production lines, the accuracy of calculations can be up to 6 times higher compared to known approaches. At the same time, the technological equipment selected according to known approaches will simply not be able to ensure the proper productivity of the technological line, since it will have extremely low productivity.